A 30 YEARS WOMAN WITH MAJOR DEPRESSIVE DISORDER WITH PSHYCHOTIC SYMTOMPS - Prataganta Iradat (Fakultas Kedokteran Universitas Lampung, 2014)
Depression is a common mental disorder that appears with a sad mood, loss of interest, decreased of energy, low self-esteem, sleep or appetite disturbance, and decreased of concentration. This disorder incidence is increased with the increasing senescence. Women, 30 years old, with a chief complaint of delusion that she had already died. Because of this, she often attempted suicide. From anamnesis found that patient in low mood, kept silent and abstracteded, lost appetite and pull away from the environment. Psychiatric status found the general impression of the patient seen untidy in dressing, facial features appropriate with age, sadexpression, lack of concentration, mood/affective was sad/hypothimia. The way of thinking was less productive, coherent, relevant, with no language impairment, the contents of thought are nihilistic delusions and delusions of guilt. There are hallucinations and illusions. The insight level was 1. Multiaxial diagnosis are axis I: major depressive episode with psychotic symptoms; axis II and III: currently not found; axis IV: problems with primary support group (family); axis V: GAF 60-51. Patients received psychotherapy and pharmacotherapy in the form of fluoxetine, risperidone. Mental disorders experienced by patients due to various factors. Therefore,the patient need cooperative support and good communication from physicians, patients herself, and families. [J Agromed Unila 2014; 1(3):222-227]Keywords: depression, depressive disorder, mood, pshychotic